2021
DOI: 10.1093/jcag/gwab017
|View full text |Cite
|
Sign up to set email alerts
|

Do Low-Risk Patients With Dyspepsia Need a Gastroscopy? Use of Gastroscopy for Otherwise Healthy Patients With Dyspepsia

Abstract: Background Choosing Wisely Canada (CWC) recommends not to perform gastroscopy for dyspepsia in otherwise healthy adults less than 55 years of age (2014). The aim of this study was to evaluate the use of gastroscopy in a young, healthy population with uncomplicated dyspepsia. Methods A retrospective review of gastroscopies completed during 3-month periods in 2015, 2016, and 2017 identified all patients undergoing gastroscopy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Limitations are that it was single centre, with a questionnaire response rate of 33%, although the findings of low diagnostic yield in those without alarm features is supported by other recent studies from the West. [13][14][15][16] Our study was performed in secondary care, with a mixed referral pattern, and the findings may not be applicable outside these clinical settings (e.g. in the community) where arguably the yield will be even lower.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Limitations are that it was single centre, with a questionnaire response rate of 33%, although the findings of low diagnostic yield in those without alarm features is supported by other recent studies from the West. [13][14][15][16] Our study was performed in secondary care, with a mixed referral pattern, and the findings may not be applicable outside these clinical settings (e.g. in the community) where arguably the yield will be even lower.…”
Section: Discussionmentioning
confidence: 93%
“…The results are consistent with recent studies from the West (Canada, United States, Netherlands, and Sweden) which, having used a broader definition of dyspepsia, noted that almost a third to a half of upper GI endoscopies performed within GI clinics are in low risk dyspeptic patients without alarm features, in whom significant endoscopic findings were low, with malignancy rare. [13][14][15][16] To our knowledge, our study is the first evaluating this issue within the UK whilst using the Rome IV criteria.…”
Section: Discussionmentioning
confidence: 98%
“…None of the study investigators had a financial incentive to perform endoscopies. Similarly, a study conducted in Canada reported that 65% of gastroscopies performed in patients with dyspepsia were based on the presence of alarm signs; 20 however, other study carried out in United Kingdom found that only 14.8% of gastroscopies in dyspeptic patients associated red flags 21 …”
Section: Discussionmentioning
confidence: 99%
“…В ретроспективном исследовании 2021 г. из 1 358 пациентов с неисследованной диспепсией 35% были отнесены в группу низкого риска выявления эндоскопических находок -их возраст составил от 18 до 54 лет, отсутствовали симптомы тревоги и сочетанные заболевания, патологические изменения лабораторных показателей. В этой группе при ЭГДС не было выявлено ни одного случая онкологического заболевания, а значимые эндоскопические находки выявлены в 3,3% случаев [14].…”
Section: симптомы определениеunclassified